Eine modulare gesundheitsakte als antwort auf kommunikationsprobleme im gesundheitswesen = A modular electronic health record as an answer to communication problems in health care - Schwarze, Jan-Christoph; Ückert, Frank (Wirtschaftsinformatik, 2005)
Since 2000 the University of Muenster has developed an electronic health record (EHR) called „akteonline.de“. Several clinics and departments use the EHR in routine. „akteonline.de“ in its current structure supports patients as well as health care professionals and aims at providing a collaborative health information system which perfectly supports the clinical workflow even across institutional boundaries. In order to fulfill high data security and data protection requirements strictly, complex encryption, authorization and access control components have been developed.The IT-structure of the German health care system is very heterogeneous and peripheral. The thereby generated additional costs in the economic and social area are comprehensible and the patient is unable to claim the central position intended by politics and society. The development effort of „akteonline.de“ currently focuses on the introduction of an electronic foundation for an „integrated care“. For that communication possibilities for different clinical systems, like systems for physician or clinical information systems as well as communication possibilities between different departments in a hospital or networking between Institutions and the patient himself, have to be provided. The various needs of the institutions and people involved, have to be considered individually within one concept.Based on gathered experiences and with regard to increasing requirements in the areas of interoperability, integration and international cooperation the system architecture and the basic data model underwent several evolutionary enhancements. The focus of this paper lies on describing the use of new technologies and open standards in order to create and enhance a loosely coupled, modular and flexible EHR, that represents a common information and communication tool for patients and health care professionals.